From Poussin to Matisse : The Russian Taste for French Painting - The Metropolitan Museum of Art, New York (Chicago : The Art Institute of Chicago, 1990)
Boilly, Louis Léopold ; Bonnard, Pierre ; Boucher, François ; Cézanne, Paul ; Lorrain, Claude ; David, Jacques Louis ; Fragonard, Jean Honoré ; Gauguin, Paul ; Gérard, François ; Greuze, Jean Baptiste ; etc.
From Poussin to Matisse: The Russian Taste for French Painting, The Metropolitan Museum of Art, New York, from May 20 to July 29, 1990, and at The Art Institute of Chicago from September 8 to November 25, 1990
boek
Keywords: Rusland; Frankrijk